KNOWLEDGE, AWARENESS, AND PRACTICES REGARDING BIOMEDICAL WASTE MANAGEMENT AMONG UNDERGRADUATE DENTAL STUDENTS - Kumar mp, Santhosh; Rahman, Reshma (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study was to assess the knowledge, awareness, and practices of dental students regarding biomedical waste (BMW)management. Methods: A self-administered structured questionnaire consisting of 16 questions on knowledge, awareness, and practices about BMW managementwas distributed among 100 students randomly belonging to 3rd year, final year and intern students of Saveetha Dental College, Saveetha University,Chennai. The data extracted were tabulated, statistically analyzed using SPSS version 20.0 and results obtained. The data were analyzed using ANOVAtest (all the results are calculated at 1% level of significance) and Post-hoc test. Results: Overall, 67% respondents were aware of the existing BMW management policy systems in India. 62% of students were aware about thecorrect color coding management system for hospital waste management that prevails in India. 86% of students knew about the dental wastecategories of materials used in dentistry. There was a statistically significant difference of knowledge levels among the 3rd year, final year students andthe interns. 100% practice discarding sharps in the puncture-proof containers. Only 27% of the respondents discarded the extracted tooth in a properway. Only 51% of them have attended previous training programs on dental waste management. There was also a statistically significant difference ofBMW disposal practices among the three groups. Conclusion: The majority of dental students in our study have good level of knowledge and awareness regarding BMW management in dental clinics.However, their practice toward BMW disposal was poor. Hence, the knowledge acquired must be put into practice. Intern students have the highestlevel of knowledge and practices toward dental waste disposal when compared to final year and 3rd year students. Hence, these findings imply thatproper training, continuing education programs, and short-term courses about BMW management, and infection control procedures are requiredto motivate the dental students and dental auxiliaries. The importance of training regarding BMW management must be emphasized as the lack ofproper and complete knowledge about BMW management impacts practices of appropriate waste disposal.